PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI PENDEKATAN PEMBELAJARAN BERDIFERENSIASI PADA PELAJARAN IPAS DI KELAS IV SDN 07 SUNGAI JAMBU KABUPATEN TANAH DATAR - Asmaul Husna; Arwin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is motivated by the reality that occurs in the field. Students' lack of understanding of the subject matter provided at school has an impact on students' low learning outcomes. The aim of this research is to provide an overview of improving student learning outcomes in science and science lessons using a differentiated learning approach using a problem based learning model in class IV at SDN 07 Sungai Jambu, Tanah Datar Regency.This research is Classroom Action Research (PTK) with a qualitative and quantitative approach. The subjects in this research were teachers and 22 students. The research data consists of the results of teaching module assessments, the results of observations of the implementation of learning using a differentiated learning approach in science lessons and student learning outcomes using a differentiated learning approach.The results of this research show an increase from cycle I to cycle I. The results of observations of the teaching module in cycle I obtained an average score of 81.25% with good qualifications (B) and an increase in cycle II of 93.75% with very good qualifications ( SB). The teacher aspect in cycle I was 84.38% and increased in cycle II, namely 93.75% with very good qualifications (SB). The student aspect of cycle I was 78.12% with sufficient qualifications (C), increasing in cycle II to 90.63% with very good qualifications (SB). Student learning outcomes in cycle I obtained an average score of 74.42 with sufficient qualifications (C) with a completion percentage of 81.81% and increased in cycle II to 81.70 with good qualifications (B) with a completion percentage of 95.45%. It can be concluded that the differentiated learning approach can improve student learning outcomes.